The Bear Grylls Adventure. Book 2, The Desert Challenge [anglicky] - Grylls, Bear (Bear Grylls Ventures, 2019)
The second magical adventure tale from popular survival expert, Bear Grylls. Sophie has been given the magical compass which transports her to the desert on a survival adventure with Bear Grylls, but can she overcome her phobia of creepie-crawlies for good when she's back in the real world?